Pengaruh Keahlian dan Kepatuhan Kode Etik terhadap Kualitas Audit - ELA SUSILA; YUNITA KURNIA SHANTI (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2017)
This study aims to determine the effect of the expertise and code of ethics compliance to audit quality. This study was conducted in South Tangerang City Inspectorate. The independent variable in this study is the expertise and compliance with a code of ethics. The dependent variable is the quality of the audit.This research is a quantitative study with descriptive approach. The data used is primary data and secondary data. Respondents in this study were government officials in South Tangerang City Inspectorate. The sampling technique used was simple random sampling with 49 respondents. Methods of collecting data using a survey questionnaire distributed to respondents. Data were analyzed using multiple regression analysis with SPSS version 22. The results of this study show that first expertise has significant effect on audit quality, it is based on the calculation of the t test is sig. 0.021 <0.05 and t count (2.399)> t table (2,012). Second, the compliance code of conduct affects the quality of audits, it is based on the calculation of the t test is sig. 0.000 <0.05 and tcount (5.286)> t table (2,012). Third, expertise and compliance with the code of conduct simultaneously affect the quality of audits, it is based on the calculation of F test value (121.020)> F table (3.20).